1980
DOI: 10.1002/dev.420130207
|View full text |Cite
|
Sign up to set email alerts
|

Development of between‐limb movement synchronization in the chick embryo

Abstract: Spontaneous between-limb movement synchronization is described as the amount of concurrent limb movement observed in 7--19-day chick embryos. At early stages, a wing moved as often with the ipsilateral leg as with the contralateral wing. Later, between-girdle (ipsilateral wing-leg) synchronization progressively decreased and within-girdle (wing-wing) synchronization increased, especially after 15--17 days. Bilaterally synchronized movements of the wings as in flapping and of the legs as in walking appeared at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Fourth, 2-to 10-Hz limb excursions emerged at E15-E18, and during the faster movements, mixed muscle synergies were produced resembling EMG patterns during the paw shake in cat. Fifth, wing and leg movements were intermittently coordinated E9 -E18, but an in-phase pattern at E9 and out-of-phase pattern at E18 were the most distinct, confirming and extending an earlier observational study of motility in ovo (Provine 1980).…”
Section: Discussionsupporting
confidence: 85%
“…Fourth, 2-to 10-Hz limb excursions emerged at E15-E18, and during the faster movements, mixed muscle synergies were produced resembling EMG patterns during the paw shake in cat. Fifth, wing and leg movements were intermittently coordinated E9 -E18, but an in-phase pattern at E9 and out-of-phase pattern at E18 were the most distinct, confirming and extending an earlier observational study of motility in ovo (Provine 1980).…”
Section: Discussionsupporting
confidence: 85%
“…The increased frequency of bilaterally-synchronized (within-girdle) wing movements during development was correlated with a decrease in the between-girdle synchronization of movements of the homolateral wing and leg (Provine, 1980). Although behavioral observations indicate that between-limb synchronization emerges gradually during embryogenesis, electromyographic evidence indicates that within-limb coordination in the legs and, by inference, probably in the wings is present from very early stages (Bekoff, 1976).…”
Section: Provine Discussionmentioning
confidence: 95%
“…The present results suggest that these presumptive locomotor precursors show not only synergistic contractions of the muscles of a single limb, but alternating movement between the 2 limbs in a manner analogous to the bilateral coordination of mature walking. Similarly, interlimb coordination developed significantly ahead of function in the chick (Provine, 1980), mouse (Fentress, 1978), rat (Bekoff & Trainer, 1979), and cat (Brown, 1915). Bekoff (1976) reported that in the chick embryo, coordi- nated motor output could be detected in the antagonistic muscles of a single leg as early as 7 days, although bilateral coordination was not well-developed until 17 days, a few days before hatching (Provine, 1980).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, interlimb coordination developed significantly ahead of function in the chick (Provine, 1980), mouse (Fentress, 1978), rat (Bekoff & Trainer, 1979), and cat (Brown, 1915). Bekoff (1976) reported that in the chick embryo, coordi- nated motor output could be detected in the antagonistic muscles of a single leg as early as 7 days, although bilateral coordination was not well-developed until 17 days, a few days before hatching (Provine, 1980). Since both single-leg and alternating kicks are seen at birth in humans, observations of full-term infants cannot answer the question of whether intralimb coordination matures well before or concurrent to interlimb coordination.…”
Section: Discussionmentioning
confidence: 97%